2020
DOI: 10.3389/fpsyg.2020.579514
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Sensitivity Moderates the Association Between Father-Child Relationship Security and Fear Transmission

Abstract: Observational fear learning can contribute to the development of fear-related psychopathologies, such as anxiety disorders and post-traumatic stress disorder. Observational fear learning is especially relevant during childhood. Parent-child attachment and anxiety sensitivity modulate fear reactions and fear learning but their impact on observational fear learning has not been investigated. This study investigated how these factors contribute to observational fear learning in children. We examined this question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 62 publications
1
12
0
1
Order By: Relevance
“…Beyond main effects of EE and anxiety on child psychophysiological responding to threat, and consistent with growing evidence for Person × Environment interactions (Bilodeau-Houle et al, 2020;Gilissen et al, 2007;La Buissonnière-Ariza et al, 2019), EE and anxiety may exacerbate or attenuate the effects of one another. One possibility is that parents' attempts to socialize high anxious children through EE may be especially counterproductive because of these children's potential overarousal in the face of stressful circumstances.…”
Section: Parenting Influences On Threat and Safety Learningsupporting
confidence: 71%
See 3 more Smart Citations
“…Beyond main effects of EE and anxiety on child psychophysiological responding to threat, and consistent with growing evidence for Person × Environment interactions (Bilodeau-Houle et al, 2020;Gilissen et al, 2007;La Buissonnière-Ariza et al, 2019), EE and anxiety may exacerbate or attenuate the effects of one another. One possibility is that parents' attempts to socialize high anxious children through EE may be especially counterproductive because of these children's potential overarousal in the face of stressful circumstances.…”
Section: Parenting Influences On Threat and Safety Learningsupporting
confidence: 71%
“…However, observed effects were specific to the safety stimulus. Even though prior work largely supports hypotheses regarding trait and parenting influences on response to threat cues (Bilodeau-Houle et al, 2020;Lissek et al, 2005), the trend observed in the current study is also in line with previous findings that anxious individuals exhibit enhanced responding to conditioned safety cues (Lissek et al, 2005), and that individuals high in trait anxiety show stronger fear responding to the safety stimulus, but not the threat stimulus, during acquisition (Duits et al, 2015;Gazendam et al, 2013). In addition, some studies also observe that children exposed to extreme harsh par- Several strengths mitigate these limitations and offer preliminary data about the role fathers play in their daughters' threat and safety learning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have indicated that anxiety affects attentional capacity and learning (Helsen et al, 2011;Bilodeau-Houle et al, 2020), as well as stress responses in terms of cortisol levels. Fiksdal et al (2018) study, for example, showed that anxiety levels increased hypothalamic-pituitary-adrenal axis reactivity to social stress.…”
Section: Introductionmentioning
confidence: 99%